An OX40L mRNA vaccine inhibits the growth of hepatocellular carcinoma - Deng, Zhuoya; Yang, Hao; Tian, Yuying; Liu, Zherui; Sun, Fang; Yang, Penghui (Frontiers in Oncology, 2022)
mRNA cancer vaccines show therapeutic potential for malignant tumors, including hepatocellular carcinoma (HCC). We optimized and synthesized stable mRNA encoding costimulator Oxford 40 ligand (OX40L). For systemic delivery, OX40L mRNAs were loaded into lipid nanoparticles (LNPs). The expression and costimulatory effects of OX40L were investigated in vitro. OX40L was expressed on the cell surface and costimulated T cells. In vivo, intratumoral injection of LNPs encapsulating OX40L mRNAs significantly reduced tumor growth and increased the survival of mice bearing H22 tumors. Importantly, CD4+ and CD8+ T cells were significantly increased in the OX40L mRNA group in vivo. Taken together, our findings provide a promising clinical strategy for immunotherapy for HCC using mRNA vaccines.